STUDIES OF DAMAGE TO THE WHEELSET FREIGHT CARS IN OPERATION IMPACT OF BRAKE SYSTEM - Vodianikov, Yu. Ya.; Kukin, S. V.; Nishchenko, O. Ye. (Science and Transport Progress, 2007)
Results of research of damageability of surface of wheelsets in operation, caused by the impact of brake shoes in braking are provided. Statistical characteristics of damage occurrence depending on the term of service have been received.